Porous Optically Transparent Cellulose Acetate Scaffolds for Biomimetic Blood-Brain Barrierin vitro Models - Marino, Attilio; Baronio, Micol; Buratti, Umberto; Mele, Elisa; Ciofani, Gianni (Frontiers in Bioengineering and Biotechnology, 2021)
In vitro blood-brain barrier (BBB) models represent an efficient platform to conduct high-throughput quantitative investigations on BBB crossing ability of different drugs. Such models provide a closed system where different fundamental variables can be efficaciously tuned and monitored, and issues related to scarce accessibility of animal brains and ethics can be addressed. In this work, we propose the fabrication of cellulose acetate (CA) porous bio-scaffolds by exploiting both vapor-induced phase separation (VIPS) and electrospinning methods. Parameters of fabrication have been tuned in order to obtain porous and transparent scaffolds suitable for optical/confocal microscopy, where endothelial cell monolayers are allowed to growth thus obtaining biomimetic BBB in vitro models. Concerning VIPS-based approach, CA membranes fabricated using 25% H2O + 75% EtOH as non-solvent showed submicrometer-scale porosity and an optical transmittance comparable to that one of commercially available poly(ethylene terephthalate) membranes. CA membranes fabricated via VIPS have been exploited for obtaining multicellular BBB models through the double seeding of endothelial cells and astrocytes on the two surfaces of the membrane. Electrospun CA substrates, instead, were characterized by micrometer-size pores, and were unsuitable for double seeding approach and long term studies. However, the potential exploitation of the electrospun CA substrates for modeling blood-brain tumor barrier and studying cell invasiveness has been speculated. The features of the obtained models have been critically compared and discussed for future applications.